Analisis Biaya Produksi (Cost Of Production) Dalam Menentukan Harga Jual Menggunakan Metode Full Costing - Suci, Desi Permoni; Nusantoro, Jawoto; Septiani, Ana (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the difference in the calculation of production costs according to mushroom production with the calculation of production costs using the full costing method. And to find out the selling price of production according to straw mushroom production and according to the full costing method. The research method used in this research is qualitative research. The research results show that there is a price difference, namely by using the full costing method, the price obtained is greater than the cost of production obtained according to business processor estimates. This is because the classification and collection carried out by business processors does not take into account all costs sacrificed. because the calculations made by business processors are not correct in imposing factory overhead costs on each product